Optimalisasi Layanan Dana Pensiun Lembaga Keuangan (DPLK) melalui Pengelolaan Manfaat Pensiun Berkala, Manfaat Lain, dan Iuran Sukarela - Syarifudin Yunus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to describe the level of service optimization in Financial Institution Pension Funds (DPLK) through the management of periodic pension benefit payments, additional benefits, and voluntary contributions using a descriptive-analytical approach. The data were derived from reports of 24 DPLK administrators collected in April 2026. The findings indicate that service optimization is largely determined by the effectiveness of managing periodic pension payments, other pension benefits, and contributions beyond the core program. This issue becomes crucial when viewed from DPLK performance trends over the past five years (2021–2025), where collected funds—comprising contributions and investment returns—were consistently lower than pension benefit payments, with an average ratio of 63%. This imbalance highlights sustainability concerns. The study identifies significant untapped potential, including Rp5.79 trillion annually (36% of total pension benefits) in periodic payments not yet optimized, Rp2.4 trillion for other benefit programs over 10 years, Rp1 trillion for religious-related funds, and Rp1.2 trillion in voluntary contributions from existing participants. To address these gaps, DPLK institutions need to strengthen regular and personalized communication beyond transactional interactions, ensuring participants are more engaged. Integrated services that emphasize transparent benefits, ease of contribution, continuous financial education, and digital accessibility are essential. Ultimately, optimizing DPLK services requires not only system and product improvements but also attention to participant behavior and service quality to enhance retirement well-being.